(untitled) (IPS Journal of Public Health, 2023)
Background: Starvation may alter energy metabolism and physiological activity of the gonads, with their cyclic production of sex hormones and this may affect reproduction. Aim: The aim of the study is to investigate the effects of intermittent and severe starvation on some female reproductive hormones in female albino Wistar rats. Methods: Thirty adult female albino rats weighing 160-180g were randomly subdivided into three groups-A, B and C. Group A serves as control and was fed with rat chow and water. Group B were subjected to intermittent starvation of food, each rat was fed 1g of feed and 2mls of water daily for 7 days. Group C was subjected to severe starvation of food, each rat fed with 1g of feed and 2mls of water daily for 14 days. The animals were sacrificed at the end experiment and blood samples were collected through cardiac punctures and stored in sterile plain containers. Serum FSH, LH, progesterone and estrogen were measured by enzyme-linked immunoassays for each group of rats. Results: The mean levels of FSH, LH, progesterone and estrogen were significantly lower in acutely and chronically starved rats (5.96± 0.32; 4.01 ± 0.29 vs 6.40 ± 0.64) when compared with the control (p <0.005). The mean levels of all the assayed hormones in chronically starved rats (group C) were found to be significantly reduced when compared with the acutely starved rats (group B) (p <0.005). This study indicated that starvation may result in decreased release of FSH, LH, estrogen and progesterone.